Copper Electrodeposition from a Water-Containing Choline Chloride Based Deep Eutectic Solvent. (7th July 2017) - Valverde, Priscila; Green, Todd; Roy, Sudipta
Abstract : This study investigated the effect of water on the physical and electrochemical properties of a choline chloride deep eutectic solvent (DES). Physical and electrochemical measurements were performed on the DES containing varying amounts of water. When the water content was increased from 1% to 15 wt%, the viscosity and density declined while the conductivity increased significantly. Similarly, the limiting current for Cu reduction at 15 wt% of water was also found to be three times greater than the limiting current at 1 wt% of water. This latter effect could be mostly attributed to viscosity changes, but there was evidence of deviations from ideal Stokes-Einstein behaviour. These experimental results show that inclusion of water facilitates ion mobility, and generally results in improved electrochemical characteristics.